Fuzzy Direct Torque Control of Electric Vehicle with Dual Induction Motors Fed by Five Leg Inverter - Kadri, Farid; Hamida, Mohamed Assaad (University of Eloued جامعة الوادي, 2022)
Thre are several possible EV configurations regarding the electric propulsion and the energy sources. In conventional dual-motor configuration, tow three phase VLSI inverters are associated to dual induction motors drives. A novel structure is to associate only Five Legs Inverter (FLI) to drive the dual induction motors of the electric vehicle. In order to improve performance setting, a Fuzzy Direct Torque Control technique has been applied by using five legs inverter instead of six legs inverter to control the electric vehicle. The proposed Fuzzy Direct Torque Control can ensure the decoupling control and distribute the required torques to 1.5-kW dual induction motors drives. Simulations in SIMULINK/MATLAB environment are carried out to show that the developed fuzzy control is effective and provides a simple configuration with good performance in terms of speed and torque responses.
Forum Intervention of Artificial Intelligence and Its Applications. Faculty of Exat science. University of Eloued
Keywords: Direct Torque Control (DTC), Dual Motor Drive, Induction Motor, Fuzzy Logic Control, Five Legs Inverter (FLI), Voltage Source Inverters (VSI).